2021
DOI: 10.33774/chemrxiv-2021-jtrqb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universal Nanopore Platform Integrating Multiple Resistive Pulse Sensors into a Single Microfluidic Device

Abstract: Resistive pulse sensors have been used to characterise everything from whole cells to small molecules. Their integration into microfluidic devices have simplified sample handling whilst increasing throughput. Typically, these devices measure a limited size range or a specific analyte, making them prone to blockages in complex sample matrixes. To prolong their life and facilitate their use, samples are often filtered or prepared to match the sample with the sensor diameter. Here, we advance our tuneable flow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Within the literature, a range of materials have been tested for RPS applications, and some of the most common solid-state materials are SiN and SiO 2 . 43 In keeping with our philosophy to create an easy to fabricate and assemble device, we opted to first create pores using pulled glass capillaries. A pipette was mounted into the screw thread shown in Fig.…”
Section: Sensormentioning
confidence: 99%
“…Within the literature, a range of materials have been tested for RPS applications, and some of the most common solid-state materials are SiN and SiO 2 . 43 In keeping with our philosophy to create an easy to fabricate and assemble device, we opted to first create pores using pulled glass capillaries. A pipette was mounted into the screw thread shown in Fig.…”
Section: Sensormentioning
confidence: 99%
“…This liquid contact can also be introduced by a droplet using a pipette tip. Recently, Wang’s group demonstrated that the applied voltage can be controlled across different membranes and generate nanopores at a specific position in the flow system [ 155 , 156 , 197 ]. They also reported that CBD nanopores formed in a localized manner at the cross-disjoint mortise structures generated by Ga-FIB etching [ 198 ].…”
Section: Localized Nanopore Fabrication By Cbdmentioning
confidence: 99%